Ethnobotany of an indigenous tree Piliostigma thonningii (Schumach.) Milne-Redh. (Fabaceae) in the arid and semi-arid areas of South Omo Zone, southern Ethiopia - Mesfin Belete Hailemariam; Zerihun Woldu; Zemede Asfaw; Ermias Lulekal (BMC, 2021)
Abstract Background Trees are important components of terrestrial ecosystems; they provide ecological, economic, and cultural services to humans. There is an urgent need for undertaking ethnobotanical investigations and documentation on the indigenous botanical knowledge of the local communities of a given area. This study was conducted to assess and document the categoric ethnobotany of Piliostigma thonningii and the associated indigenous knowledge of the local people related to use, management practices, and the threatening factors in the South Omo Zone of southwestern Ethiopia. Materials and methods Six Kebeles were purposively selected from two districts of the zone and a total of 84 respondents were sampled, with consideration of gender, age, and wealth status. Data were collected using structured and semi-structured interviews, field observations, and group discussions. Relevant descriptive statistical methods were used to analyze the data. Ethnobotanical knowledge held by informants were computed using Pearson's chi-square test and direct matrix ranking and pair-wise ranking was used to prioritize the uses according to community preferences and the level of the destructiveness of the reported threats. Results The results showed that P. thonningii provides different functions to people's livelihoods as shade, food, fodder, soil fertility, fuelwood, medicine, rope, multipurpose materials (e.g., Borketa for sitting and head support), huts, beehives, farm implements, chairs, fences, and timber. The indigenous knowledge of local people on the uses of P. thonningii has shown significant (P < 0.05) relationship to age groups (being higher for elderly people). The consumption practice of respondents has significant (P < 0.05) association to the Kebeles, age, and income, with higher value for Hamer, lower aged groups, and low-income families. It provides nutritious animal feed to improve browse intake, survival, and productivity of domestic animals and also improve productivity of farm through amelioration of soil fertility. The status of P. thonningii has been decreasing due to agricultural expansion, collection of the species for firewood, dry fencing, and due to browsing. Respondents' attitude and interest to maintain and conserve the species has shown a significant (P< 0.05) association to gender, wealth, and level of education. Higher interest was observed in men than women, mid-high wealth class households than low income, and people with education than uneducated. Conclusions This study attempted to provide information on the multiple uses of P. thonningii. Given the key roles of P. thonningii for the people and the environment to improve household food security, agricultural productivity, and income sources and the threats to it, the need to protect it in natural forests and woodlands and optimize its uses in agroforestry systems is high. Serious consideration of this species will ultimately allow households to reap the benefits expected to accrue from it in the arid and semi-arid areas of Ethiopia where plants of this nature are usually rare.